Paneth cells as the cornerstones of intestinal and organismal health: a primer - Charlotte Wallaeys; Natalia Garcia‐Gonzalez; Claude Libert (EMBO Molecular Medicine)
Abstract Paneth cells are versatile secretory cells located in the crypts of Lieberkühn of the small intestine. In normal conditions, they function as the cornerstones of intestinal health by preserving homeostasis. They perform this function by providing niche factors to the intestinal stem cell compartment, regulating the composition of the microbiome through the production and secretion of antimicrobial peptides, performing phagocytosis and efferocytosis, taking up heavy metals, and preserving barrier integrity. Disturbances in one or more of these functions can lead to intestinal as well as systemic inflammatory and infectious diseases. This review discusses the multiple functions of Paneth cells, and the mechanisms and consequences of Paneth cell dysfunction. It also provides an overview of the tools available for studying Paneth cells.